STRES DAN RESILIENSI REMAJA DI MASA PANDEMI COVID-19 - Gani Apriningtyas Budiyati; Eka Oktavianto (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2020)
The existence of a pandemic raises a sense of concern for the community. For this reason, various efforts and policies were made to tackle the spread of Covid-19, including limiting school meetings and the imposition of online learning which is one of the stressors for adolescents. To overcome these stressors, one of them is needed resilience in adolescents. The purpose of this study was to determine the relationship between resilience and stress in adolescents during the Covid-19 pandemic. This research method is a quantitative correlation study with a cross-sectional design. Sampling in this study using accidental sampling technique. The sample in this study were adolescents aged 12-18 years in the city of Yogyakarta. The number of samples in this study were 136 respondents. The instruments used in this study used a modified resilience questionnaire from Monica (2015) and a stress questionnaire with DASS-42. Bivariable analysis using the Chi-Square test. The results of this study indicate the Chi Square results with a p value of 0.001 (p <0.05) which indicates that there is a relationship between resilience and stress in adolescents. The conclusion of this study is that there is a relationship between resilience and stress in adolescents.